2021
DOI: 10.1155/2021/5585140
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practice of Nurses Working in the Adult Intensive-Care Unit and Associated Factors towards the Use of Physical Restraint in Federally Administered Hospitals in Addis Ababa, Ethiopia: A Multicenter Cross-Sectional Study

Abstract: Background. Physical restraint is any chemical or physical involuntary method restricting an individual’s movement, physical activity, or normal access to the body. Physical restraints are prescribed by the physician, but the ICU nurse remains the decision maker responsible in assessing the need, application, and removal of PR on patients in the ICU setting. Objectives. This cross-sectional descriptive study was carried out to determine the knowledge, attitudes, and practices of nurses working in adult ICU and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
3
4
0
1
Order By: Relevance
“…This result was similar to the studies reported from Australia, 22 German, 32 South Africa, 15 Embu in Kenya, 25 and Addis Ababa. 16 The result is also similar to reports in Federal Hospitals in Addis Ababa 30 and Wollega, Ethiopia. 21 The reason might be due to the use of guidelines used as a direct source of information and hold sets of systematic procedures that were expected from nurses for pressure ulcer prevention and having good knowledge.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…This result was similar to the studies reported from Australia, 22 German, 32 South Africa, 15 Embu in Kenya, 25 and Addis Ababa. 16 The result is also similar to reports in Federal Hospitals in Addis Ababa 30 and Wollega, Ethiopia. 21 The reason might be due to the use of guidelines used as a direct source of information and hold sets of systematic procedures that were expected from nurses for pressure ulcer prevention and having good knowledge.…”
Section: Discussionsupporting
confidence: 84%
“…27 South Africa, 15 Uganda, 14 Umgungundlovu District in South Africa, 28 and National Orthopedic Hospital of Enugu in Nigeria 29 show that nurses have poor knowledge of pressure ulcer prevention. Similarly, the levels of knowledge were poor in the studies conducted in Federally Administered Hospitals in Addis Ababa, 30 Gondar University Hospital, 20 Hawassa University comprehensive specialized hospital, 31 and public hospitals in Wollega 21 relative to this study finding (Figure 1). The difference might be due to a change of methodology and also might be due to increased knowledge source of information, scientific evidence, and research results, along with increased educational level of health care workers (qualification) that might also be the cause of the difference.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…As the main decision makers and practitioners, critical care nurses play a vital role in using physical restraint. Several quantitative studies explored critical care nurses' knowledge, attitudes, and behaviours towards physical restraint (Almomani et al, 2021; Ertuğrul & Özden, 2021; Woldekirkos et al, 2021). The findings showed that critical care nurses lacked knowledge about physical restraint and were unsure about using alternatives.…”
Section: Introductionmentioning
confidence: 99%